Nano technological Enhancement of Meat balls Quality - Mohebat A. Abd El - Aziz; Nahla Abo EL-Roos; Rasha El.sabagh; Hemmat M. Ibrahim; Badawi Anis (Proceedings on Engineering Sciences, 2020)
Different concentrations of two nano-materials having very small size (~ 20 nm), Zinc oxide (Zn O) with concentrations (12 mM) and Titanium dioxide (Ti O2) with concentrations (12 mM) and Mixture between Zn O + Ti O2 (6 mM) were used for improving microbial, sensory and physic-chemical properties of meatballs during storage at refrigerated temperature for 20 days. Treated meat balls samples with nanoparticles show great improvement in their bacteriological status as the aerobic plate count, psychotropic bacterial count, coliform count and staphylococcus count have been decreased, also the score of Sensory characteristics of treated meatballs such as odor, color and texture were higher than those of control sample that spoiled at 9th day. Moreover, the physico- chemical properties of treated meat ball samples such as (PH, TBA and TVB-N) were significantly (P≤0.05) different from control one throughout all storage period.